Feasibility study on implementation of medium temperature solar thermal energy in industrial processes: a case study in Malaysia / Chin Chuan Kong - Chin, Chuan Kong (2012)
A case study on the feasibility of implementing medium temperature solar thermal energy in industrial processes in Malaysia is conducted. The objective is to determine if it is technically and economically viable to utilize the solar thermal renewable energy at a temperature range of 80-250°C as a substitute to conventional means of generating thermal energy. Solar energy is the source of most other renewable energies, and Malaysia being situated at the equator makes us geographically favorable to harness this free energy. Almost half of the industrial processes use thermal energy rather than electrical energy, and the output of a solar thermal system can fit in nicely as a contributor to the industries’ energy mix. Literature reviews are conducted on the climatology of Malaysia, in particular, the solar irradiance, the technologies involved and the various industries in Malaysia are then studied to identify potential candidates to utilize this renewable energy. Also, different types of solar collector technologies are studied and explored. After that, a particular industry and its industrial process are chosen for a case study. A solar thermal system is designed and sized to fulfill needed energy requirements for the process. Then, a simulation is performed to determine the overall output of the system based on Malaysian meteorological data. Based on the results, the contribution of solar thermal energy in supplementing the plant’s energy requirement, i.e. solar fraction is determined. A cost and benefit analysis is done on the system, taking into account of initial investment and consumption cost for a period of 10 years, without consideration of maintenance cost. The results are compared with other means of generating heat, namely boiler, heat pump, electric heater and solar PV powered electric heater. It is determined that solar thermal energy provides the greatest saving. However, due to the large fuel oil subsidy by the Government currently, solar thermal system is attractive for only low temperature ranges.